2020
DOI: 10.1038/s41415-020-2402-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro virucidal activity of povidone iodine gargle and mouthwash against SARS-CoV-2: implications for dental practice

Abstract: Introduction Virus particles in respiratory droplets and aerosols generated during medical/dental procedures are a potential source of SARS-CoV-2 cross infection. In the dental setting, oral decontamination could be an important adjunct to personal protective equipment and is recommended by a number of national COVID-19 guidance documents for dental settings. Aim To assess the in vitro virucidal activity of an oral povidone iodine (PVP-I) product agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 33 publications
(39 reference statements)
4
40
0
5
Order By: Relevance
“…Although in vitro testing of PVP-I solution revealed a considerable reduction in SARS-CoV-2 viral titers, its effect on humans was unclear [1]. Our study confirms the presumed effectiveness of PVP-I in nasopharyngeal clearance of SARS-CoV-2 among COVID-19 patients.…”
Section: Discussionsupporting
confidence: 53%
“…Although in vitro testing of PVP-I solution revealed a considerable reduction in SARS-CoV-2 viral titers, its effect on humans was unclear [1]. Our study confirms the presumed effectiveness of PVP-I in nasopharyngeal clearance of SARS-CoV-2 among COVID-19 patients.…”
Section: Discussionsupporting
confidence: 53%
“…We feel that the targeted training package has addressed many of the deficits and there is significant room within the emergency medicine training programme to measure, focus and develop such content to the needs of junior doctors. 1 We hope to encourage other dental and oral and maxillofacial surgery departments to get involved in training within their respective emergency departments and recognise that this can bring benefits in the form of improved co-operation, reduced referral load for minor conditions and better patient care. the need for teacher training (TT), but the profession persists with limited guidance and no mandate for it.…”
Section: Emergency Medicine Trainingmentioning
confidence: 99%
“…Sir, I read with interest the recent paper on the recommendations to use povidone iodine mouthwash as part of routine infection prevention and control (IP&C) measures in dental practice. 1 There are several limitations in the methodology of this study that should be considered when assessing this recommendation. The authors highlight quite rightly the importance of disinfectant neutralisation to ensure '...that there were no after effects of the test product beyond the specified contact time. '…”
Section: Pw-i For All? Not Yetmentioning
confidence: 99%
“…These researchers also showed that 70% ethanol-based rinse requires a minimum contact time of 30 seconds rather than 15 seconds to completely inactivate SARS-CoV-2. Subsequent in vitro studies conducted by Hassandarvish et al 9 demonstrated potent and rapid virucidal efficacy of 0.5% and 1% PVP-I rinse at the lowest contact time of 15 seconds, and Anderson et al 10 also demonstrated the efficacy of 1.0% w/v PVP-I oral rinse and 0.45% w/v PVP-I throat spray with a contact time of 30 seconds.…”
mentioning
confidence: 98%
“…No cytotoxic effects of 1% PVP-I mouthwash have been reported when used at a concentration of 0.63 mg/mL (ie, 1:16 or lower dilution of the product). 9 Moreover, in addition to a well-established safety profile, PVP-I also exhibits good tolerability at concentrations as high as 2.5% for up to 5 months, with the absence of tooth or tongue discoloration or taste disturbances. 13 Unlike alcohol-based mouth rinse, it can also be used in conjunction with electrocautery, which also make it a suitable choice for use in maxillofacial surgery.…”
mentioning
confidence: 98%